Haemorrhagic Lumbar Juxtafacet Cyst with Ligamentum Flavum Involvement - Finn Ghent; Trent Davidson; Ralph Jasper Mobbs (Case Reports in Orthopedics)
Juxtafacet cysts are an uncommon cause of radiculopathy. They occur most frequently in the lumbar region, and their distribution across the spine correlates with mobility. Haemorrhagic complications are rare and may occur in the absence of any provocation, although there is some association with anticoagulation and trauma. We present a case of acute radiculopathy due to an L5/S1 juxtafacet cyst with unprovoked haemorrhage which was found to extend into ligamentum flavum. The patient underwent uncomplicated microscope assisted decompression with excellent results. The demographics, presentation, aetiology, and management of juxtafacet cysts are discussed.